Superior sensitive graphene fiber sensor enabled by constructing multiple nanoembossments for glucose detection - Feng Han; Yangguang Wu; Yifan Zhao; Weixuan Jing; Kun Zheng; Chenying Wang; Song Wang; Yaxin Zhang; Tao Dong; Zhuangde Jiang (Microsystems & Nanoengineering)
Abstract Metal oxides have been extensively investigated in non-enzymatic biosensors for detecting diabetes owing to their electrochemical catalytic properties and excellent stability. However, lower conductivity and catalytic activity are major obstacles to the commercialization of metal oxide-based non-enzymatic glucose sensors. Herein, we present a novel flexible nonenzymatic glucose sensor utilizing graphene fiber (GF)/Au/Ni(OH)2 composite fiber. The integration of GFs enables a significant uptake of sensing molecules due to its expansive surface area and high electron mobility, ultimately resulting in a decrease in the detection limit. Consequently, the incorporation of Ni(OH)2 provides abundant attachment sites by introducing Au atoms, thereby promoting electron migration and enhancing sensitivity and detection limits. An impressive sensitivity (1095.63 µA mM−1 cm−2) within the detection range (5 µM–2.2 mM) of the integrated GF/Au/Ni(OH)2 fiber is achieved, leading to an incredibly low detection limit (0.294 µM). Additionally, the outstanding repeatability, anti-interference properties, and flexibility of the GF/Au/Ni(OH)2 sensors are obtained as well. Our findings offer a novel method for constructing nano embossments on GFs to achieve superior glucose detection capabilities in the field of wearable electronics in the future.